Cotton noil based cellulose microfibers reinforced polylactic acid composite films for improved water vapor and ultraviolet light barrier properties. Issue 24 (15th March 2022) - Ponnusamy, Prabaharan Graceraj; Sharma, Suraj; Mani, Sudhagar
Abstract: The cellulose reinforced polylactic acid (PLA) composites are one of the most widely explored biopolymer composites in packaging applications. In this study, the cellulose microfibers (CMF) isolated from cotton noil were reinforced with 1%, 3%, 5%, 10%, and 20% in PLA matrix by solvent casting method. The strong interfacial adhesion and enhanced dispersion of CMF in PLA polymer matrix increased the tensile, water vapor, ultraviolet (UV) light barrier properties of the composites. The ultimate tensile stress and Young's modulus of 1% CMF reinforced composites were increased by 46% and 30% respectively than that of control films. A further increase in percent CMF reinforcement of up to 20% slightly reduced the tensile strength of composites but was comparable to that of low‐density polyethylene polymer. The water vapor permeability was decreased while increasing the CMF reinforcement due to the increased diffusion path by the dispersed CMF. The UV light absorbance of the composite was improved by up to 90% with the increase in CMF reinforcement by up to 20% due to the increased chromophore groups of cellulose. Hence, the PLA‐CMF composites could be used for packaging and storing light and moisture‐sensitive products. Abstract :